THE ROLE OF DAPAGLIFLOZIN AS AN ADJUNCTIVE THERAPY IN SIADH-INDUCED HYPONATREMIA - Ahmad, Khairiah Binti; Nandini, Norisha (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Syndrome of inappropriate antidiuretic hormone secretion (SIADH) leads to impaired water excretion and dilutional hyponatremia. Sodium-glucose cotransporter 2 inhibitors (SGLT2i), which were initially developed for diabetes and heart failure, have shown promise as a novel treatment for chronic SIADH-related hyponatremia based on recent studies. CASE We report the case of a 66-year-old male with comorbidities of systemic lupus erythematosus, heart failure and adrenal insufficiency on steroid replacement. His heart failure medications included furosemide, spironolactone, and dapagliflozin, which was initiated in May 2024. Prior to admission, his serum sodium levels ranged from 130–135 mmol/L. During his current hospitalization, he was treated for pneumonia and incidentally noted to be hyponatremic with a sodium level of 128 mmol/L. At this point, diuretics and dapagliflozin were withheld. He responded to fluid boluses given, showing an initial improvement in his serum sodium, which then plateaued, followed by a declining trend to a nadir of 115 mmol/L. Paired serum and urine samples sent were consistent with SIADH. Hormonal workup taken showed normal thyroid and cortisol level. The patient was then given hypertonic saline to correct the initial severe hyponatremia, followed by fluid restriction and oral salt. Despite an initial improvement, this effect was not sustained, with sodium levels remaining static at 125–126 mmol/L. Dapagliflozin was then reintroduced, resulting in progressive improvement in his serum sodium, which allowed for discontinuation of oral sodium supplementation. He showed progressive clinical improvement and was discharged well with a serum sodium of 138 mmol/L. CONCLUSION This case illustrates the potential benefit of SGLT2 inhibitors in managing SIADH-related hyponatremia. Reintroduction of dapagliflozin led to a sustained rise in sodium levels, even after discontinuing salt supplementation. SGLT2i may enhance free water clearance and could be considered as adjunctive therapy in chronic SIADH, alongside fluid restriction and sodium supplementation.